2007
DOI: 10.1007/s11709-007-0039-6
|View full text |Cite
|
Sign up to set email alerts
|

Flutter control effect and mechanism of central-slotting for long-span bridges

Abstract: The flutter control effect and mechanism of central-slotting, which have gradually been adopted in the design and construction of long-span bridges as an effective flutter controlling measure, were investigated with theoretical analysis and wind tunnel test. Five basic girder cross-sections representing five typical aerodynamic configurations were selected and central-slotted with two different slot widths. Then, a series of sectional model tests and theoretical analyses based on the two-dimensional three-degr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 2 publications
(3 reference statements)
0
5
0
Order By: Relevance
“…22 and 29), meaning that, regardless of the gap length, rather the existence of the gap itself controls these parameters; H Ã 2 , A Ã 1 and A Ã 3 are better correlated with the original Theodorsen function (Eqs. (11), (14) and (16)), independently of the gap length. As for H Ã 4 , the values exhibit an independent behavior.…”
Section: Aerodynamic Derivativesmentioning
confidence: 98%
See 2 more Smart Citations
“…22 and 29), meaning that, regardless of the gap length, rather the existence of the gap itself controls these parameters; H Ã 2 , A Ã 1 and A Ã 3 are better correlated with the original Theodorsen function (Eqs. (11), (14) and (16)), independently of the gap length. As for H Ã 4 , the values exhibit an independent behavior.…”
Section: Aerodynamic Derivativesmentioning
confidence: 98%
“…The mechanisms of such aerodynamic stabilization, however, have not been fully clarified [12][13][14]. Depending on the characteristics of the deck as a whole and the gap length, flutter onset may even decrease [13,14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chen et al (2006) investigated the mechanism of a vertical stabilizer for improving the aerodynamic stability of an open deck II-shaped section and a closed box section and found that vertical stabilizer can increase the amplitude of the heaving motion and decrease that of the rotational motion of the bridge decks. Yang et al (2007) indicated that the use of a central stabilizer with an appropriate height can improve the aerodynamic stability, but the aerodynamic stability decreases when the height of the stabilizer exceeds the critical limit. Ouyang and Chen (2016) showed that the central stabilizer promotes the formation of vortex pairs at the upper and lower decks near the center of the bridge deck by computational fluid dynamics (CFD) numerical simulation and particle image velocimetry (PIV) wind tunnel tests and enhances the participation function of the heaving motion of the bridge.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, we discussed the effects of different aerodynamic measures on the VIV of separate pairs of box girders through a wind tunnel test and tried to explain their control mechanism by using the Computational Fluent Dynamics (CFD) technology. Compared to the closed box girders, the flutter stability of the separate pair of box girders has been improved significantly, which, however, is compensated by high VIV possibility [29,30]. In order to restrain the VIV of the bridge with separate pairs of box girders, it is important to choose an appropriate aerodynamic configuration.…”
Section: Introductionmentioning
confidence: 99%